Optimising a 3D multigrid algorithm for the IA-64 architecture. (6th November 2008) - Sturmer, Markus; Treibig, Jan; Rude, Ulrich
Multigrid methods are amongst the most efficient algorithms to numerically solve partial differential equations. However, standard implementations usually cannot exploit the potential of modern processors. The IA-64 architecture transferes most complexity to the software side to provide a highly superscalar design with large caches, leading to unique control over the actual execution. Exemplified on a simple multigrid solver equation in 3D and the Itanium 2 processor, we present how known performance optimisation techniques can be successfully combined. While implementation details are specific, the optimisation concept should be applicable for a wide range of numerical algorithm and CPUs.